Down-regulation of miR-29 improves lipid metabolism in fatty liver of dairy cows - Xueying Wang; Cai Zhang; Rishun Li; Yan Qiu; Yanbo Ma; Shuai Wang; Yuanxiao Li; Shuai Guo; Chenxu Li (Animal Biotechnology)
In this study, we conducted a thorough investigation into the mechanisms by which miR-29 influences lipid metabolism. Thirty-two cows were selected and categorized into distinct groups based on their liver triglyceride (TG) content: healthy, mild fatty liver, and moderate fatty liver groups. Dairy cows with moderate fatty liver showed higher levels of hepatic lipid accumulation, MDA content and serum AST, ALT and ALP contents and lower hepatic catalase CAT and SOD activities. Subsequently, hepatocytes isolated from healthy calves were exposed to sodium oleate (SO) in the presence or absence of pre-incubation with miR-29 inhibitor or inhibitor NC. Pre-transfection with miR-29 inhibitor resulted in reduced hepatocyte lipid accumulation and MDA levels, as well as decreased levels of AST, ALT, and ALP in the supernatant. In the miR-29 inhibitor + SO group, there was an increase in the expression of SREBP-1, FAS, SCD1, and Sirt1. Meanwhile, the expression of PPARα, CPT1, CPT2, PGC-1α, NRF-1, UCP2, and miR-29 were observed to be decreased. In comparison to the miR-29 inhibitor + SO group, some of the measured indicators showed partial reversal in the miR-29 inhibitor + siSirt1 + SO group. Collectively, these findings provide evidence that miR-29 may play a crucial role in the pathogenesis of fatty liver in dairy cows.